THE REFERENCE GAREVKA GRANITE (YENISEI RIDGE, WESTERN MARGIN OF THE SIBERIAN CRATON): THE FINAL ATTEMPT TO VERIFY PALEOPROTEROZOIC Pb/U ISOTOPIC AGE BY M.I. VOLOBUEV - A. B. Kuzmichev; M. K. Danukalova (Геодинамика и тектонофизика)
The article unravels a confusing history of ideas about the age of the Garevka granite pluton, which is considered as a reference object for the Precambrian of the Yenisei ridge. Initially, the Paleoproterozoic (1750 Ma) age of granite was determined by M.I. Volobuev and co-authors half a century ago using Pb/U isotope analyses of zircons and orthites. This dating is widely used up to recent to substantiate the Early Precambrian age of the metamorphic rocks of the Trans-Angara region. In 2003, V.A. Vernikovsky and his colleagues published data on the Neoproterozoic (752±3 Ma) age of the massif, obtained with modern technique of isotopic analysis. However, some of experts on the geology of the Yenisei ridge considered both isotopic ages correct, believing that the eastern part of the massif comprises Paleoproterozoic gneissic granite. Our investigation revealed the following: V.A. Vernikovsky and M.I. Volobuev indeed have collected their granite samples at the western and at the eastern parts of the pluton correspondingly. Krasnoyarsk geologists map the Garevka pluton as part of the Neoproterozoic Glushikha granite suite, but use to apply its Paleoproterozoic dating to substantiate the early Precambrian age of the host rocks. M.I. Volobuev obtained ten mainly discordant Pb/U analyses of the Garevka granites, and six of them form an explicable combination consistent with the age of 1750 Ma. The only concordant analysis with a known sampling point is decisive for the entire system. Thus, to fix the problem, it was necessary to reproduce this analysis using modern isotope techniques. We have dated (SHRIMP) a granite sample collected at the same point. In addition, three more samples from different parts of the massif were analysed to exclude the possible presence of ancient domains in it. The isotope ratios of all analysed zircons form a concordant cluster with an age of 762±7 Ma. The Garevka pluton comprises a separate mappable body composed of biotite leucogranites with fluorite. Granites do not replace some older rocks, but crystallized from the melt, ascended from deep crust. The question about possible Paleoproterozoic age of the Garevka granite pluton or any part of it is closed. Ideas about the wide distribution of Archean and Paleoproterozoic gneisses in the Trans-Angara region require additional geochronological verification. To date, the presence of such rocks has been reliably established here only at two local points.